True story : how to combine story and action to transform your business - Montague, Ty (HighBridge Audio, 2014)
The old way to market a business was storytelling. But in today's world, simply communicating your brand's story in the hope that customers will listen is no longer enough. Instead, your authentic brand must be evident in every action the organization undertakes.